Youth athletes` self-esteem: The impact of integrated psychological skills training - Merlin, Q.; Vacher, P.; Martinent, G.; Nicolas, M. (Pediatric Exercise Science, 2024)
Purpose: Study on the effect of psychological skills training on self-esteem (SE) in young athletes.